trans activation of granulocyte-macrophage colony-stimulating factor and the interleukin-2 receptor in transgenic mice carrying the human T-lymphotropic virus type 1 tax gene. - Green, J E (1989)
Three lines of transgenic mice carrying the human T-cell lymphotropic virus type 1 tax gene have previously been reported to develop neurofibromas composed of perineural fibroblasts (S. H. Hinrichs, M. Nerenberg, R. K. Reynolds, G. Khoury, and G. Jay, Science 237:1340-1343, 1987; M. Nerenberg, S. H. Hinrichs, R. K. Reynolds, G. Khoury, and G. Jay, Science 237:1324-1329, 1987). Tumors from these mice and tumor cell lines derived from them expressed high levels of tax RNA and protein. They also expressed high levels of the granulocyte-macrophage colony-stimulating factor (GM-CSF) gene as measured by proliferative responses of FD-CP1 target cells using conditioned media from tumor cells and by Northern (RNA) blot analysis of RNA from tumors and tumor cell lines. Although other tissues, such as salivary glands and muscles, in the transgenic mice also expressed high levels of tax, they did not express the gene for GM-CSF. This indicates that tissue-specific cellular factors, in addition to tax, are required for GM-CSF gene expression. Systemic effects of excessive GM-CSF production were demonstrated by infiltration of polymorphonuclear leukocytes into tumor tissues which are not necrotic, by peripheral granulocytosis, and by splenomegaly resulting from myeloid hyperplasia. The interleukin-2 (IL-2) receptor was also found to be expressed by the tumors and tumor cell lines as measured by IL-2-binding and cross-linking studies. This is the first demonstration that the IL-2 receptor can be activated by tax in a nonlymphoid cell type. These in vivo findings are consistent with other reports which have demonstrated in vitro cis-regulatory elements within the 5'-flanking regions of the genes for GM-CSF and the IL-2 receptor which are responsive to trans activation by the tax gene.